A CRITICAL ANALYSIS OF VALUE CREATION WITH ADVANCES OF TECHNOLOGY IN INDIAN HEALTHCARE SYSTEM - Swarup, Ritesh Kumar; Roy, Sourabh Singha; Verma, Sudhanshu (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper explores the transformative role of technology in creating value within the Indian healthcare sector through detailed case studies of pioneering organizations and initiatives. Apollo Hospitals, Aravind Eye Care, Practo, and the Ayushman Bharat Digital Mission exemplify how digital health tools—including telemedicine, artificial intelligence, electronic health records, and interoperable health ecosystems—are enhancing accessibility, affordability, efficiency, and patient empowerment. These case studies demonstrate that integrating technology with context-sensitive operational models can improve healthcare delivery while addressing India’s unique socio-economic challenges. The analysis highlights both the successes and ongoing challenges, such as infrastructural gaps, digital literacy, and data privacy concerns. This study underscores the critical need for inclusive, scalable, and ethical technological adoption to achieve sustainable and equitable healthcare outcomes in India.